HCI in Business, Government and Organizations: 9th International Conference, HCIBGO 2022, Virtual Event, June 26 - July 1: Proceedings - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2022)
This book constitutes the refereed proceedings of the 9th International Conference on HCI in Business, Government and Organizations, HCIBGO 2022, held as part of the 23rd International Conference, HCI International 2022, which was held virtually in June/July 2022. The total of 1271 papers and 275 posters included in the HCII 2022 proceedings was carefully reviewed and selected from 5487 submissions. The HCIBGO 2022 proceedings focuses in topics such as artificial intelligence and machine learning, blockchain, service design, live streaming in electronic commerce, visualization, and workplace design.